2019
DOI: 10.3390/min9120749
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Preservation of Fungi as H2-Bearing Fluid Inclusions in an Early Quaternary Paleo-Hydrothermal System at Cape Vani, Milos, Greece

Abstract: The production of H2 in hydrothermal systems and subsurface settings is almost exclusively assumed a result of abiotic processes, particularly serpentinization of ultramafic rocks. The origin of H2 in environments not hosted in ultramafic rocks is, as a rule, unjustifiably linked to abiotic processes. Additionally, multiple microbiological processes among both prokaryotes and eukaryotes are known to involve H2-production, of which anaerobic fungi have been put forward as a potential source of H2 in subsurface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 116 publications
(225 reference statements)
1
8
0
Order By: Relevance
“…Powder XRD (PXRD) data (Table S1) confirm previous mineralogical investigations [41][42][43]46,48]. The presence of micro-and nano-crystalline todorokite cement has been revealed for the first time by means of PXRD, BSE-EDS, FEG-SEM and HR-TEM investigations.…”
Section: Mineralogical and Textural Characterization Of Todorokitesupporting
confidence: 82%
See 2 more Smart Citations
“…Powder XRD (PXRD) data (Table S1) confirm previous mineralogical investigations [41][42][43]46,48]. The presence of micro-and nano-crystalline todorokite cement has been revealed for the first time by means of PXRD, BSE-EDS, FEG-SEM and HR-TEM investigations.…”
Section: Mineralogical and Textural Characterization Of Todorokitesupporting
confidence: 82%
“…Field relationships, combined with fluid inclusion data from hydrothermal barite and quartz, suggest that the MnMISS developed in a very shallow (<50 m) steaming marine paleo-environment, in close association with white smoker-type seafloor activity that probably acted as Mn(II) supplier. The temperatures were~125 • C at depth (feeder veins) cooling to <100 • C near and at the paleo-seafloor in response to boiling, mixing with seawater and conductive heat loss [43,62]. Sulphur (δ 34 S) and oxygen (δ 18 O) isotope evidence has shown that the investigated MnMISS are younger than 1.5 Ma, and possibly formed about 0.5 Ma ago [43]; moreover, the MnMISS associated barite was derived from seawater sulphate that has undergone some alteration through bacterial sulphate reduction (BSR) [43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the characterization of biomarkers has not yet been successful enough to use as a discriminating factor to distinguish between groups like eukaryotes or prokaryotes. An exception is chitin, which was detected by staining with WGA-FITC under fluorescence microscopy and thus could be used as an indicator for the presence of fungi (Ivarsson et al, 2012(Ivarsson et al, , 2019bBonneville et al, 2020).…”
Section: Fossil Record In Igneous Oceanic Crustmentioning
confidence: 99%
“…Fluid circulation and mixing in fractures and during vein formation can lead to metal leaching and accumulation of ores, such as those in the Harz mountains, Germany [1]. Microbial activity in fractured rock volumes can also be of importance for ore-forming processes [2,3] and may involve potentially significant microbial natural gas accumulations [4,5]. Furthermore, microbial activity and fluid flow may involve important redox processes and fluctuations that are relevant for safety [30,38].…”
Section: Introductionmentioning
confidence: 99%